Sistem Pembiayaan Pendidikan Islam Berbasis Kemandirian Ekonomi Lembaga - Helfyna Desrita; Hamdi Abdul Karim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The financing system in Islamic education plays a crucial role in maintaining the continuity and quality of educational services. This paper aims to discuss the concept and practice of implementing an Islamic education financing system that focuses on the economic independence of the institution. Through the literature study method and descriptive-analytical approach, this research reveals that the financing pattern based on economic independence is developed through the optimization of institutional assets, productive waqf management, utilization of zakat, infaq, and sadaqah (ZIS) funds, and the establishment of independent business units. The findings show that Islamic educational institutions that are able to realize economic independence can reduce dependence on external funding, strengthen financial stability, and strengthen their position in developing long-term educational programs. This model also contributes to community economic empowerment through synergy between the education and business sectors based on Islamic principles. Therefore, strengthening the economic management of the institution is a key aspect of creating a sustainable and quality financing system. This study recommends the need for innovative and collaborative strategies in managing economic resources to support the realization of independent and competitive Islamic education financing.